The Time-Space Regimes of Human Mobility in the North Atlantic Island Spaces (Iceland, Azores, Madeira, the Canary Islands, and Cape Verde) - Luis Manuel Jerez-Darias; Josefina Domínguez-Mujica (Island Studies Journal)
Throughout history the North Atlantic archipelagos have projected themselves outwards thanks to travel and the innate capacity of their inhabitants to relate to other peoples. This research aims to reveal their nodal character on the stage of global mobility, using a detailed statistical analysis of their migration trends since the 1960s. To this end, it is necessary to recognise the rhythms of the migration transition and its parallelism with the socio-economic development of the island spaces themselves. In addition, common features can be identified in their recent migration patterns in which a great diversification of origins and destinations predominates, as well as a multiplicity of motivations. With this aim, migration in these archipelagos is interpreted from a temporal and spatial perspective, redefining the historical concept of "Atlanticity," and allowing to identify the strategic position they play in the geography of human mobility in times of global capitalism.